A 606 W burst-mode picosecond Yb-doped all-fiber laser with an intra-burst repetition rate of 469 MHz - Xinyao Li; Haijuan Yu; Shuzhen Zou; Chaojian He; Chaoyu Ning; Wenjuan Wu; Xuechun Chen; Xuechun Lin (High Power Laser Science and Engineering)
This paper introduces a novel fiber-based picosecond burst-mode laser system capable of operating at high power and high repetition rates. A pulse-circulating fiber ring was developed as a burst generator, achieving an intra-burst repetition rate of 469 MHz without the need for a high-repetition-rate seed source. This design also allows for flexible adjustment of the number of sub-pulses, burst repetition rate and burst shape. In addition, a master oscillator power amplifier was employed to analyze the amplification characteristics of bursts. The system demonstrated a maximum average power of 606 W, with a measured sub-pulse duration of 62 ps and the highest sub-pulse peak power of 980 kW. To the best of our knowledge, this marks the highest average power obtained in burst-mode ultrafast lasers. Such a laser system holds potential for applications in precision manufacturing, high-speed imaging, high-precision ranging and other diverse domains.